Pration and characteristics of the In-doped ZnO thin films the n-ZnO :In/p-Si heterojunctions for optoelectronic switch - Canh, Ta Dinh; Tuyen, Nguyen Viet; Long, Nguyen Ngoc; Ha, Vo Ly Thanh (VNU Journal of Science: Mathematics - Physics; Vol 26 No 1, 2010)
Abstract